Urban cowboys needed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A shortage in skilled livestock managers was a key problem to emerge from ten studies on urban agriculture sponsored recently by Canada s International Development Research Centre. Under IDRC s Agropolis programme to support post-graduate research...